Factors affecting dental prosthesis satisfaction in Pakistani population - Ahmed, Naseer; Faruqui, Saba (International Journal of Dental Research, 2015)
The purpose of this clinical study was to determine the level of patients satisfaction after prosthodontic treatment.This cross sectional study was conducted in Altamash Institute of Dental Medicine, a total of 200 partially edentulous patients already restored with removable or fixed prosthesis participated in this study. Patient satisfaction was evaluated by Likert's scale. The Patients were given options of unsatisfied, not very satisfied, neutral, somewhat satisfied and satisfied to evaluate patients level of satisfaction for factors such as phonetics, pain, mastication, taste and esthetics.After statistical analysis, Likert scale score's positively for all factors such as phonetics, pain, mastication, taste and esthetics.After prosthodontic treatment patients show high level of satisfaction with their prosthesis though showing positive impact of prosthesis on oral health.